Adab Ilmuwan Menurut Abū Ḥanīfah (M.150H): Suntingan Ilmiah, Terjemahan dan Analisis Waṣiyyah Abī Ḥanīfah li Tilmīdhih Yūsuf al-Samtī: Rules of Conduct for Islamic Scholars According to Abū Ḥanīfah (D.150H): A Critical Edition, Malay Translation and Analysis of His Waṣiyyah Abī Ḥanīfah li Tilmīdhih Yūsuf al-Samtī - Mamat, Mohd Anuar; Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
The great works of Muslim scholars are among the main resources for any studies on Islam including on Islamic education. This article presents a critical edition of one of the great work by Imam Abū Ḥanīfah on Islamic education entitled Waṣiyyah Abī Ḥanīfah li Tilmīdhih Yūsuf al-Samtī together with an introduction and Malay translation. The text contains counsel and essential discussion about the rules of conduct for Islamic scholars. This edition is based on four manuscripts, namely the manuscript of the British Library, London, Suleymaniyyah Kutuphanesi, Istanbul, King Sa‘ūd University, Riyad and Islamic University, Madinah. In addition, the quotation of the text by al-Muwaffaq al-Makkī (d.586H) and al-Kurdarī (d.827H) was also considered and compared in this edition. This study presents this great work on Islamic education to the modern reader for the benefit of trying to solve the current ethical and educational problems.